Assessment of energy efficient rocket stoves contribution on deforestation control in Tanzania: A case study of Chamwino District in Dodoma Region - Gerome, Annamaria Cornelius (2023)
A Dissertation Submitted in Partial Fulfillment of the Requirements for Award of the Degree of Master of Science in Environmental Management (MSc. EM) of Mzumbe University